2005
DOI: 10.1029/2005je002401
|View full text |Cite
|
Sign up to set email alerts
|

Fluid lava flows in Gusev crater, Mars

Abstract: [1] Rocks on the floor of Gusev crater are basaltic in composition, as determined from measurements by the Mars Exploration Rover, Spirit. On the basis of compositional data, models of the basaltic lavas at the time of their emplacement suggest viscosities of 2.3 to 50 Pa Á s (dependent on the number of phenocrysts and vesicles that were present), which would be more fluid than terrestrial tholeiitic lavas and comparable to mare lavas on the Moon or Archean high-Mg basalts on Earth. Morphological data and crat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
120
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(127 citation statements)
references
References 36 publications
7
120
0
Order By: Relevance
“…The temperature of multiple saturation, 1320 °C, is within the temperature range of Earth's basaltic magmatism (1280-1475 °C) (e.g., Kinzler and Grove 1992;McKenzie and Bickle 1988), indicating that conditions for Martian basalt production would be characterized by high mantle potential temperatures, similar to those on modern Earth. Greeley et al (2005) suggest that the basalts emplaced on the floor of Gusev crater may be temporally related to volcanic activity on the southern side of Apollinaris Patera and may be the result of regional volcanism around 3.65-3.76 Gyr. This indicates that high mantle potential temperatures, similar to those on modern Earth, persisted on Mars for at least 1.0 Gyr, until the end of the Noachian era.…”
Section: Melting Processesmentioning
confidence: 99%
See 2 more Smart Citations
“…The temperature of multiple saturation, 1320 °C, is within the temperature range of Earth's basaltic magmatism (1280-1475 °C) (e.g., Kinzler and Grove 1992;McKenzie and Bickle 1988), indicating that conditions for Martian basalt production would be characterized by high mantle potential temperatures, similar to those on modern Earth. Greeley et al (2005) suggest that the basalts emplaced on the floor of Gusev crater may be temporally related to volcanic activity on the southern side of Apollinaris Patera and may be the result of regional volcanism around 3.65-3.76 Gyr. This indicates that high mantle potential temperatures, similar to those on modern Earth, persisted on Mars for at least 1.0 Gyr, until the end of the Noachian era.…”
Section: Melting Processesmentioning
confidence: 99%
“…Age estimates of the Gusev basalt from crater counting are Late Noachian to early Hesperian (3.7 Gyr) (Greeley et al 2005). Therefore, the early Martian lithosphere beneath the Gusev site would have been thin and mantle conditions would have allowed melting to occur.…”
Section: Melting Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…1). Although there is no absolute age information, these diverse basalts are found in a Hesperian terrain that is estimated to have formed ∼3.7 billion years ago (Greeley et al, 2005). Importantly, Gusev basalts are samples of the Martian interior at an earlier time than the shergottites.…”
Section: Introductionmentioning
confidence: 99%
“…Richardson et al (2013) revealed three major episodes activity of fields of several hundred vents between 2.56 and 3.52 Ga as the Syria Planum region evolved from a central ventvolcano to dispersed volcanism. The lavas flooding of Gusev Crater, the landing site of the Mars Exploration Rover Spirit, were dated at 3.65 Ga (Greeley et al, 2005b), postdating other floor materials such as hypothesized sediments from Ma'adim Vallis. The lava flows emplaced on the floor of Gusev Crater have similar crater count ages as volcanic activity on the southern flank of Apollinaris Patera, which could reflect a general regional volcanic episode (Greeley et al, 2005b).…”
Section: Volcanismmentioning
confidence: 99%